A Cuff-shaped Enzymeless Glucose Sensor Integrated with Chronically Implantable Peripheral Nerve Cuff Electrode for Inflammation Monitoring - Lee, Yi Jae; Park, Sung Jin; Kang, Ji Yoon; Lee, Soo Hyun (2015 7TH INTERNATIONAL IEEE/EMBS CONFERENCE ON NEURAL ENGINEERING (NER), 2015)
This paper reports on a recently developed cuff-shaped enzymeless glucose sensor integrated with chronically implantable peripheral nerve cuff electrode for the reflecting nerve signal degradation, particularly in the time immediately following implantation. The cuff-shaped enzymeless glucose sensor with black Pt working electrode (WE) showed the roughness factor (RF) of 16.413 and extremely lowered impedance of 40 ohm at 1 kHz compared to the plain Pt (RF: 1, impedance 600 ohm). The enzymeless glucose sensor with black Pt WE operated without any enzyme and mediators. It exhibited dramatically increased glucose sensitivity of 38.26 mu A/mMcm(2) and detection limit of 25 mu M in the glucose range up to 16 mM. These results indicate that the fabricated glucose sensor is promising for the inflammation monitoring application in the immediate vicinity of the implantable nerve cuff electrodes.